Configuration of maximum power point tracking (MPPT) with boost converter / Muhamad Safwan Muhamad Zainuldin - Muhamad Zainuldin, Muhamad Safwan (2011)
The main purpose of this project is to observe types of configurations using photovoltaic (PV) boost converter modules for maximum power point tracking (MPPT) might be affect by load. There are three types of loads that use in this simulation which are resistive load, voltage load, and current load. Then, PV modules connected in single, parallel, and series converter with using this three type of loads to compare the calculation value and simulation value. The most important model component in the PV modules is the solar module.